PERLINDUNGAN HUKUM TERHADAP PARA PIHAK AKIBAT PEMBATALAN AKTA PPJB TANAH: STUDI DI KANTOR NOTARIS KOTA TANGERANG SELATAN - Setiawan, Adam; Hungan, Fani Clarais (Jurnal Ilmiah Advokasi, 2025)
A Notary's practice is based on Law Number 2 of 2014 concerning the Position of Notary. A Notary is a public official authorized to create authentic deeds, one of which is the Deed of Sale and Purchase Binding Agreement (PPJB). The PPJB is a preliminary agreement that leads to the execution of a sale and purchase transaction. In practice, agreements do not always align with expectations and may need to be canceled. Article 1338 of the Civil Code states that agreements made by the parties act as laws that apply to those who create them. Therefore, further analysis is needed regarding the practice of canceling a PPJB agreement, as well as the legal protection and legal consequences for the parties involved in the cancellation of the PPJB deed at Notary Offices within the jurisdiction of South Tangerang City. This issue was analyzed using normative legal research methods. The findings show that Article 1338 of the Civil Code stipulates that agreements must be carried out in good faith. Based on this provision, any agreement by the parties to cancel a contract must be based on good faith, reflecting the mutual intention of the parties when the cancellation deed is made. Legal protection for both the seller and the buyer is outlined in the clauses of the Deed of Cancellation of the PPJB. Based on the content of the cancellation, all prior binding agreements in the original PPJB deed are nullified. The Deed of Cancellation of the PPJB serves as a binding law for the parties, adhering to the principle of good faith, and constitutes the legal consequence of the canceled PPJB due to the emergence of new provisions that must be agreed upon and implemented by the parties. Keywords: Legal Protection, Notary, Agreement, PPJB Agreement